2021
DOI: 10.22271/j.ento.2021.v9.i2f.8509
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of avoidable yield losses in bitter gourd due to melon fruit fly, Bactrocera cucurbitae (Coquillett)

Abstract: The estimation of crop losses is essential for the scheduling of integrated management tactics as it helps to determine priorities on the basis of relative importance of pests. Cucurbits, the most economically nutritious crops, suffer a quiet high damage by fruit flies. Therefore, the current investigation was carried out to estimate the avoidable yield losses due to melon fruit fly, Bactrocera cucurbitae in the bitter gourd variety 'Pusa Do Mausami'. The study was conducted at Experimental Area,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…To understand the potential long‐term efficacy of the protein‐bait trap, we used simulations to estimate the number of viable offspring prevented from introduction into the population, by considering the number of eggs traps that would prevent from being laid (via the trapping of female flies). A set of assumptions for the simulation was generated by collecting life‐history information on B. cucurbitae from a review of existing literature (Balas et al, 2018; Gaddanakeri & Rolania, 2020; Harwood et al, 2013; Kaur & Rup, 2002; Laskar, 2013; Mir et al, 2014; Mukherjee et al, 2007; Patel & Patel, 2018; Pradhan et al, 2020; Rahaman et al, 2015; Sohrab et al, 2018; Vayssières et al, 2008; Yang et al, 1994). Focusing on laboratory studies using fly populations of Indian origin, we collated a master table (Table 1), which was used to extract values relating to length of each life stage, fecundity and lifespan of B. cucurbitae females.…”
Section: Methodsmentioning
confidence: 99%
“…To understand the potential long‐term efficacy of the protein‐bait trap, we used simulations to estimate the number of viable offspring prevented from introduction into the population, by considering the number of eggs traps that would prevent from being laid (via the trapping of female flies). A set of assumptions for the simulation was generated by collecting life‐history information on B. cucurbitae from a review of existing literature (Balas et al, 2018; Gaddanakeri & Rolania, 2020; Harwood et al, 2013; Kaur & Rup, 2002; Laskar, 2013; Mir et al, 2014; Mukherjee et al, 2007; Patel & Patel, 2018; Pradhan et al, 2020; Rahaman et al, 2015; Sohrab et al, 2018; Vayssières et al, 2008; Yang et al, 1994). Focusing on laboratory studies using fly populations of Indian origin, we collated a master table (Table 1), which was used to extract values relating to length of each life stage, fecundity and lifespan of B. cucurbitae females.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative damage occurs because the fruits are damaged in certain parts or in all parts of the fruit (Heriza et al, 2013). For example, the yield loss of bitter gourd due to B. cucurbitae attack was 36.24% (Pilania et al, 2021). Asmare and Hassen's (2018) study found that the damage by fruit ies could reach up to 33.3 -66.7% for guava, and 29.2 -44.4% for sweet orange in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Gourds are cultivated in 310 ha in Tiruvallur district with bitter gourd alone occupying 125 hectares.Farmers cultivate hybrid bitter gourds in Kadambathur, Thiruvalangadu, Thiruthani and Ekadu blocks [6][7][8][9][10]. Hence it was proposed to popularize Integrated Pest management module through frontline demonstrations for effective management of pests in Bitter gourd in Tiruvallur district.…”
Section: Introductionmentioning
confidence: 99%